SAT0271 THE "GOLD STANDARD" DIAGNOSTIC TEST FOR GCA IS THE WHOLE GCA FAST TRACK PATHWAY COMBINED. (2nd June 2020) - Quick, V.; Hughes, M.; Chan, C. H.
Abstract : Background: We have been developing a rheumatologist-led ultrasound driven giant cell arteritis (GCA) fast-track pathway (FTP), which in year 3 had the following structure: 1. Rapid access to rheumatology assessment (RAS ) to establish clinical probability of GCA (CP-GCA). No referral criteria required 2. Temporal and axillary artery ultrasound (TAUS ) if GCA not excluded with RAS. TAUS considered positive if bilateral (halo score ≥2/8 1, 2 at >1 temporal artery) 3. Second test in selected patients: GCA diagnosed in those with mod-high CP-GCA and +ve TAUS and excluded in those with low CP-GCA and -ve TAUS. All others had biopsy (TAB) or large vessel imaging (LVI), presentation depending 4. Protocolised withdrawal of prednisolone: Patients only treated for GCA if ≥1 of: high CP-GCA, +ve TAUS, TAB or LVI 5. Rapid access if symptoms recurred on steroid withdrawal for RAS + TAUS Objectives: To compare security of GCA diagnosis, sight loss rate and TAB rate in Year 3 to previous years To assess sensitivity and specificity of all components of the Yr 3 FTP for diagnosis of GCA Methods: As in Yr 2, TAUS was performed by VQ with an Esaote Mylab7, 6-15MHz probe for axillaries, 22MHz for temporal arteries (TAs). In Yr 1 VQ used a GES8 with ML6-15 for axillaries, 18MHz probe for TAs. Year 3 audit data were compared to previous audits Results: Conclusion: Unlike Yr 2, the higher secure diagnosis rate in Yr 3 could not be attributed to shorter time on prednisolone or better equipment. The increase was likely due to several factors including further improved sonographer skill and increased confidence to withdraw steroids in insecure cases with low/moderate CP-GCA. This approach did not increase sight loss. Further reduction in TAB rate financially justified a 3rd FTP slot/wk created in Yr 3. Each component of the FTP was an inadequate diagnostic tool. Combinations of diagnostic tools are needed to obtain the highest sensitivity and specificity for GCA diagnosis. FTPs limit tests to the minimum required for secure diagnosis. The "gold standard" diagnostic test for GCA is the whole FTP combined. References: [1]Schäfer et al Rheum (Ox ) 2017:56(9);1479-83 [2]van der Geest et al ARD doi: 10.1136/annrheumdis-2019-216343 Disclosure of Interests: Vanessa Quick Consultant of: Roche, Speakers bureau: Roche, Mark Hughes: None declared, Chi-Hwa Chan: None declared